Monte carlo determination of correction factors for dosimetric measurements in gamma knife perfexion small fields. (September 2016) - Zoros, E.; Pappas, E.P.; Moutsatsos, A.; Pantelis, E.; Paraskevopoulou, C.; Georgiou, E.; Karaiskos, P.
Abstract : Introduction: In the formalism proposed by Alfonso et al . (2008) for the dosimetry of small and non-standard photon fields, Monte Carlo (MC) simulation is indicated as a proper means for determining machine-specific reference field ( k Q msr, Q f msr, f ref ) and clinical radiation fields ( k Q clin, Q msr f clin, f msr ) correction factors (CFs) assigned to calibration and relative dosimetry measurements, respectively. Purpose: To determine CFs for the Gamma Knife Perfexion (PFX) radiosurgery unit for a variety of commercially available detectors utilizing MC simulations. Materials and methods: A recently introduced EGSnrc comprehensive simulation model for the PFX irradiation unit was used. A set of 13 ionization chambers, 6 diodes detectors, TLD microcubes and alanine pellets were simulated based on blueprints provided by the vendors. CFs calculations were performed using the egs_chamber user code. Intermediate Phase Space Scoring and photon cross section enhancement variance reduction techniques were implemented in order to increase time efficiency. MC calculations were performed by a super-computer consisting of 8520 computational threads achieving a combined statistical uncertainty of 0.3%. Results: Calculated k Q msr, Q f msr, f ref for ionization chambers commonly used for reference dosimetry in PFX were up to 1.02 (IBA-CC01). Calculations for k Q clin, Q msr f clin, f msr revealed an overestimation of diode detectors up to 6% for the 4mm-collimator, while CFs for ionization chambers (active volume ⩽0.04cm 3 ) reached 1.48 (PTW-31015). Conclusion: A set of CFs were determined for the PFX unit allowing for more accurate dosimetry measurements. Disclosure: This work was supported by computational time granted from the Greek Research & Technology Network (GRNET) in the National HPC facility -ARIS- under project ID pr001027.